The Unmet Healthcare Needs: Evidence from Serbia - Milos MITRASEVIC; Snezana RADOVANOVIC; Svetlana RADEVIC; Milena MARICIC; Ivana Zivanovic MACUZIC; Tatjana Kanjevac (Tehran University of Medical Sciences, 2020)
Background: We aimed to determine the socio-economic factors associated with unmet healthcare needs of the population aged 20 and over in Serbia. Methods: We used data from the 2013 National Health Survey (NHS) of the population of Serbia. We focused only on the data concerning the population aged 20 and over. The final sample thus included 13,765 participants. The logistic regression was used to examine the socio-economic factors associated with unmet health care needs. Results: According to the data obtained in this study, 26.2% of the population aged 20 and over reported unmet health care needs during the previous 12 months. The multivariate analysis shows that significant indicators of unmet healthcare needs include: gender, age, marital status, level of education, financial and employment status. Conclusion: Females, the elderly and those with the lowest levels of education and household income, as well as those who are divorced and unemployed are at highest risk of unmet healthcare needs. Different policies and approaches should be taken into consideration when it comes to vulnerable population groups in order to reduce the currently existing gaps to a minimum and provide more equal opportunities for health care to all citizens.